Jeffrey Gitomer's little gold book of yes! attitude : how to find, build, and keep a yes! attitude for a lifetime of success & happiness. - Gitomer, Jeffrey H (Sound Wisdom, 2017)
Offers a step-by-step, fully integrated game plan for understanding and mastering one's attitude, revealing ways to maintain one's intensity, drive, and commitment.